Electric Mode Excitation in the Atmosphere by Magnetospheric Impulses and ULF Waves - Pilipenko, V. A.; Fedorov, E. N.; Martines-Bedenko, V. A.; Bering, E. A. (Frontiers in Earth Science, 2021)
Variations of vertical atmospheric electric field Ez have been attributed mainly to meteorological processes. On the other hand, theory of electromagnetic waves in the atmosphere, between the bottom ionosphere and Earth’s surface, predicts two modes, magnetic H (TE) and electric E (TH) modes, whereas the E-mode carries vertical electric field Ez. Past attempts to find signatures of ULF (periods from fractions to tens of minutes) disturbances in atmospheric electric field gave contradictory results. Recently, study of ULF disturbances of Ez became feasible thanks to project GLOCAEM, which united stations with 1-sec measurements of potential gradient. These data enable us to address long-standing problem of the coupling between atmospheric electricity and space weather disturbances at ULF time scales. Transmission of storm sudden commencement (SSC) impulses to lower latitudes was often interpreted as excitation of the electric TH0 mode, instantly propagating along the ionosphere–ground waveguide. We have examined simultaneous records of magnetometers and electric field-mills during >50 SSC events in 2007-2019 in search for signatures of E-mode. However, Ez disturbance never exceeded background fluctuations ~10 V/m, much less than expected for TH0 mode. Also, we have re-examined results of earlier balloon-born electric field and ground magnetic field measurements in Antarctica. We constructed a model of the electromagnetic ULF response to an oscillating magnetospheric field-aligned current incident onto the realistic ionosphere and atmosphere. The model is based on numerical solution of full-wave equations in the atmospheric-ionospheric collisional plasma, which parameters were reconstructed using the IRI model. We have calculated vertical and horizontal distributions of magnetic and electric fields of both H- and E-modes excited by magnetospheric field-aligned current. The model predicts that the excitation rate of the E-mode by magnetospheric disturbances is low, so only a weak Ez response with a magnitude of ~several V/m can be produced by ~100 nT geomagnetic disturbance. However, at balloon heights (~30 km) electric field of the E-mode becomes dominating. Predicted amplitudes of horizontal electric field in the atmosphere induced by Pc5 pulsations and travelling convection vortices, about tens of mV/m, are in good agreement with balloon – ground magnetometer observations.